2022
DOI: 10.3390/diagnostics12010097
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Blood and Salivary pH Levels in Healthy, Gingivitis, and Periodontitis Patients before and after Non-Surgical Periodontal Therapy

Abstract: Periodontitis is an infectious illness which leads to the inflammation of protective tissues around the teeth and the continuous loss of alveolar bone and conjunctive tissue. Biomarker analysis in serum and saliva helps in the evaluation of disease progression and activity. It is also established that every inflammatory change along with resultant damage of tissues ends up in altered pH values in the fluids and tissues. Aim: To correlate the connection of pH levels in both blood as well as saliva in healthy, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…The test toothpaste increased salivary pH to a slightly alkaline pH with a mean of 7.5, being more favorable for oral eubiosis 30 . The pH value is important for preserving correct cell biochemistry and tissue homeostasis, and it is low at sites with inflammation or cell destruction 31 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The test toothpaste increased salivary pH to a slightly alkaline pH with a mean of 7.5, being more favorable for oral eubiosis 30 . The pH value is important for preserving correct cell biochemistry and tissue homeostasis, and it is low at sites with inflammation or cell destruction 31 .…”
Section: Discussionmentioning
confidence: 96%
“…It was recently demonstrated that periodontal pathogens grow in a moderately acid environment, e.g., pH of 5.0-7 for P. intermedia, pH of 5.5-7 for F. nucleatum, and pH of 6.5-7 for P. gingivalis. Also, the salivary pH of patients with periodontitis became more alkaline after scaling and root planning 30 . A recent study described both salivary flow and pH as markers of periodontitis severity, which was correlated with low pH values (6.25 in www.nature.com/scientificreports/ grade IV periodontitis) and low salivary flow (0.28 mL/min); conversely, pH and flow values were significantly increased in patients with severe periodontitis after 3 months of periodontal treatment (hygienization) 33 .…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in salivary pH is the significant factor aggravating chemical corrosion and galvanic corrosion [ 100 , 118 ]. The decrease in salivary pH is commonly observed in patients with periodontal disease [ 119 ] and in patients with multiple caries [ 120 ]. Moreover, many systemic diseases and conditions may change the electrochemical characteristics of saliva [ 112 , 121 , 122 , 123 , 124 , 125 , 126 ].…”
Section: Factors Affecting the Risk Of Dental Alloys Side Effectsmentioning
confidence: 99%
“…Apart from other oral environmental conditions, i.e., nutrition, atmosphere, and redox potential [ 6 ], dental biofilm growth rate may be influenced by temporary alterations of oral acidity or alkalinity [ 6 , 7 ]. The mean pH of saliva is 6.7, within the normal range of 6.2–7.6 [ 8 ]. The resting oral pH may vary between 5.0 and 9.0 depending on different factors, including age [ 9 ], gender [ 9 , 10 ], season, and even time of day [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…At neutral pH, saliva inhibits bacterial glycolysis, thus preventing the development of anaerobic conditions [ 7 ]. Values below 7.0 indicate acidity; at this pH, the oral cavity is more susceptible to dental caries, periodontal diseases, and halitosis [ 8 , 22 ]. A study by Takashi et al showed that the growth of periodontal pathogens ( P. intermedia , F. nucleatum , and P. gingivalis ) occurs mainly at a pH of 5.0–7.0 [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%